Intellectual Property Rights in Agriculture: Plant Variety Protection and Food Security - Sugeng, Sugeng; Aidy, Widya Romasindah; Jr, Andre Cardenas (Universitas Muhammadiyah Malang, 2024)
This research explores the complex relationship between Intellectual Property Rights (IPRs) in agriculture, focusing on plant variety protection and food security. In this context, protecting plant varieties becomes key to enhancing agricultural productivity, addressing climate change challenges, and ensuring the sustainability of the food supply. Implementing intellectual property rights in agriculture also directly impacts the welfare of farmers and other stakeholders in the agricultural sector. Methodologically, this research adopts a normative approach, using various data sources and relevant analyses within the legislative framework. The research also elucidates the crucial role of institutions tasked with implementing plant variety protection measures within a broader IPR framework. The research findings indicate challenges and opportunities inherent in implementing plant variety protection measures, including legal and policy barriers, and opportunities for policy innovation and collaboration among government stakeholders, industry, and society. In conclusion, this research offers valuable insights into the complex dynamics between Intellectual Property Rights in agriculture, particularly plant variety protection, and food security. Furthermore, policy recommendations are proposed to strengthen regulatory frameworks for plant variety protection, enhance access to agricultural technology, and promote multi-stakeholder collaboration. Considering the complexity of the relationship between various aspects of IPR, plant variety protection, and food security, further research can explore innovative solutions to overcome existing barriers and capitalize on emerging opportunities. This may involve a more detailed analysis of existing legal and policy frameworks and exploring the practical implications of the policy recommendations outlined in the abstract in ensuring the sustainability of agricultural systems and food security in the future.